Menstrual health and hygiene in Brazil: A literature review (Research, Society and Development, 2023)
Menstruation is a physiological process that affects approximately 52% of women of reproductive age. Menstrual health, including proper hygiene management, is neglected in many communities and by public agencies. Improper management of menstrual hygiene can lead to health problems such as female reproductive tract infections, as well as social impacts. Research is needed to better understand these phenomena and raise awareness of the topic. This study seeks to analyze the Brazilian literature on menstrual hygiene and its implications for women's health. An integrative review was performed on the PUBMED and Google Scholar databases. The following descriptors were used: “Hygiene”, “Menstruation”, “Impacts on Health”; “Poverty” and “Brazil”. Eleven original works were included, published between 2018 and April 2023. The analyzed studies involved populations from different Brazilian regions. Concerns related to lack of access to menstrual hygiene products, menstrual health awareness and sanitary services were found in five papers. Another five surveys highlighted the importance of menstrual dignity as a fundamental aspect of the right to health for vulnerable women. And one study reported a significant advance in menstrual hygiene through the introduction of menstrual cups. In conclusion, the research revealed challenges faced by the Brazilian female population, such as the shortage of adequate menstrual products, lack of awareness about menstrual hygiene, and inadequate sanitary facilities. These findings highlight the need for adequate public interventions to improve this issue in Brazil.